Diabetogenic effect of statins: a comprehensive review on the clinical relevance, underlying pathomechanisms and rationale for tailored statin therapy - Małgorzata Ostrowska; Piotr Adamski; Marek Koziński; Eliano Pio Navarese; Jacek Kubica (Folia Medica Copernicana)
Statins are potent hypolipidemic drugs effectively reducing low-density lipoprotein (LDL) cholesterol serum concentration, but also exerting a wide range of pleiotropic effects. In numerous clinical trials statins were proven to substantially decrease cardiovascular morbidity and mortality both in primary and secondary prevention. However, a growing body of evidence suggests that statins, although safe and generally well-tolerated, are associated with an increased occurrence of new-onset diabetes mellitus (DM). The aim of this review is to explore the relationship between statin therapy and new-onset DM, including its clinical relevance and underlying pathomechanisms, and to discuss the concept of tailored statin therapy. According to our recently published comprehensive network meta-analysis including 113,394 patients, the high-dose statin regimens were connected with an elevated risk of new-onset DM as compared with moderate-dose statin regimens and a gradient for the risk of new-onset DM across different types and doses of statins was demonstrated. There are multiple possible mechanisms explaining the diabetogenic effect of statins (e.g., decreased insulin secretion, induction of b-cell apoptosis, increased insulin resistance or compromised glucose transport into the cells). Statins are among the most widely used drugs worldwide and physicians should be aware of the fact that there is a risk of new-onset DM across different types and doses of statins. Selection of adequate statin that suits patient’s needs remains the challenge of hypolipidemic therapy. The identification of individuals who would benefit more from smaller doses and/or use of less diabetogenic compounds could help to optimize the treatment and reduce the number of patients developing DM. The non-pharmacological approach such as adequate physical activity, weight reduction and low fat diet should not be neglected either. These actions create a chance to decrease baseline LDL-cholesterol concentration and reduce the number of both cardiovascular and DM risk factors. All in all, statins with their exceptional cardiovascular benefits will undoubtedly defend their position of a cornerstone of cardiovascular prevention because profits derived from statin therapy far exceed the potential harms connected with statin-induced impairments of glucose metabolism.